2020
DOI: 10.1002/star.201900137
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prata Banana (Musa AAB‐Prata) Starch: Native and Modified by Annealing

Abstract: Prata variety banana starch is little known and has great economic potential due to its extensive cultivation in developing countries. This study characterizes this native starch and modifies by annealing at different temperatures (45, 50, and 55 °C). The native starch presents a high apparent amylose content (46.67%), besides it showing granules of several sizes and shapes containing rounded ends, which remain unchanged with the annealing. The weaker crystals are seen to be strengthened by the treatments at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Furthermore, the annealing process might induce changes in both amylose and amylopectin, resulting in an amorphous structure and crystal structure. During annealing, the rearrangement of starch granules and interactions with other molecules, such as amylose, amylopectin, lipids, and proteins, led to a stronger starch structure, restricting swelling and reducing susceptibility to stirring action [36,37]. This was supported by the previous results that the peak viscosity of ANN treatment was higher at approximately 3-fold time than that of PBF treatment.…”
Section: Pasting Properties Of Modified Banana Floursupporting
confidence: 59%
“…Furthermore, the annealing process might induce changes in both amylose and amylopectin, resulting in an amorphous structure and crystal structure. During annealing, the rearrangement of starch granules and interactions with other molecules, such as amylose, amylopectin, lipids, and proteins, led to a stronger starch structure, restricting swelling and reducing susceptibility to stirring action [36,37]. This was supported by the previous results that the peak viscosity of ANN treatment was higher at approximately 3-fold time than that of PBF treatment.…”
Section: Pasting Properties Of Modified Banana Floursupporting
confidence: 59%
“…Setback viscosity (SV) is an indirect measure of starch retrogradation tendency and is a property that helps to estimate starch gel stability during storage, especially when the starch is subjected to low temperatures (cooling and freezing) (Barros et al, 2021; Kaur et al, 2007). SV value observed for C. allouia starch is considered to be low (0.86 ± 0.01 Pa.s), which indicates that the studied starch has a good paste stability to cold or a slow retrogradation (Almeida et al, 2020). Barros et al (2021) observed BV and SV values of 1.55 and 2.12 Pa.s, respectively, for starch of G. allouia .…”
Section: Resultsmentioning
confidence: 98%
“…The native ulluco starch showed low lipid content 0.11 ± 0.01%, ash content 0.12 ± 0.02%, and MC of 11.0 ± 1.0%, which can be associated with a high purity extraction product. These components are considered impurities due to the limited ability to bind covalently to the polysaccharides making up the starch granules, affecting the starch's technological performance (de Almeida et al, 2020). These results agree with the values reported by various Andean tubers (Cruz et al., 2016).…”
Section: Resultsmentioning
confidence: 99%